Multi-Objective Optimization and Decision Making for Spatial Layout of Sponge Facilities - ZHANG Dongqing; DING Xiangyi; WANG Jia; SONG Tianxu; MA Mengyang (Renmin Zhujiang)
The risk of urban flooding and non-point source pollution intensifies due to climate change and urbanization.Sponge city,a nature-based solution to adapt to climate change,is being promoted in China.How to plan and design sponge facilities to give full play to their diversified benefits becomes the key to effectively constructing a sponge city.In this study,a multi-objective optimization coupling model was constructed based on the NSGA-Ⅲ algorithm and SWMM.TOPSIS method was used to screen out the optimization scheme,and the hydrological benefits,environmental benefits,and irrigation water demand of the optimization scheme under hydrological years with high,normal,and low flows were analyzed.The method was applied to Dongshan Campus of Shanxi University.The results indicate that the three optimal schemes show good hydrological and environmental benefits under typical hydrological years,with an average annual runoff reduction rate of 68.3% and an SS reduction rate of 83.7%.Scheme S1 is the closest to the ideal scheme and has the largest irrigation water demand, which is about 228 000 m3 per year. Scheme S3 has a large proportion of vegetation sponge facilities and the highest utilization rate of rainwater, with an annual average of 141 000 m3.